Unmet weight loss targets in real-world clinical practice: weight management and perceptions in China - Ziwei Lin; Si Si; Jia Liu; Hao Zhu; Jiawei Xu; Esther Artime; Swarna Khare; Victoria Higgins; Andrea Leith; Shen Qu; Shen Qu (Frontiers in Endocrinology)
AimsTo describe weight management and perceptions in China.Materials and methodsData were from the Adelphi Real World Obesity Disease Specific Programme™, a cross-sectional survey between April and July 2022 of physicians managing people with obesity or overweight (PwO) and PwO in real-world clinical practice in China. At data collection, eligible PwO were aged ≥18 years, under weight management and/or had a body mass index (BMI) ≥28 kg/m2.ResultsIn total, 100 physicians and 801 PwO were enrolled. More than two thirds of PwO (70.7%; 531/751) were not diagnosed with obesity until a BMI ≥30 kg/m2. Most PwO (78%; 625/801) were on treatment for at least one obesity-related complication (ORC). Physicians commonly initiated weight loss discussions with PwO who already had an ORC (48.0%; 48/100). According to physicians and PwO, the mean target BMI was set at 25.8 kg/m2 and 24.3 kg/m2, and the mean target percentage weight loss was 19.6% and 23.7%, respectively. Over a median 6.4 months of weight management, the mean percentage weight loss was 4.1%. Few PwO achieved the weight loss target set by their physician (9.9%; 69/695) or themselves (2.0%; 14/696). Most physicians and PwO were unsatisfied with the current weight loss (92.3% [739/801] and 82.0% [650/793], respectively).ConclusionsThese findings suggest that earlier intervention may be needed to address obesity as a disease. Most physicians and PwO recognized the importance of normal weight, but few PwO achieved weight loss targets, which may suggest an unmet need for improved weight management.